Pemberdayaan Masyarakat dan Pendaftaran Hak Merk Olahan Moringa oleifera Menjadi Cookies Remunggai (Morcis) di Kelurahan Penurunan, Bengkulu - Utami, Risnita Tri; Waliamin, Janusi; Nurseha, Nurseha (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2022)
The coronavirus (Covid-19) has spread rapidly in various parts of the world since December 2020. This virus has caused various impacts including death and a decline in the world economy. The community service program was carried out by Prof. Dr. Hazairin, SH University (Kukerta Unihaz) is expected to be a solution in the midst of this covid-19 pandemic. This program aims to educate the public regarding the benefits of remunggai, process remunggai into cookies, and register intellectual property rights for the remunggai cookies (Morcis). The service program was carried out in Penurunan sub-district, which is one of the villages that are close to Prof. University. Dr. Hazairin, SH University. The method used in this activity were education, training, and registration of intellectual property rights. The results of the activity showed that the enthusiasm of the community regarding the benefits and processing of remunggai into cookies was relatively high, this could be seen from the large number of people who took part in this activity, which consisted of sub-district employees, PKK women, youth group, Small and Medium Enterprise in Penurunan sub-district.